Understanding the relationship between Mycobacterium bovis spoligotypes from cattle in Latin American Countries - Zumarraga, Martin Jose (2013)
Spoligotyping is the most frequently used method for genotyping isolates of Mycobacterium bovis worldwide. In the current work, we compared spoligotypes from 1684 M. bovis isolates from Argentina (816), Brazil (412), Chile (66), Mexico (274) and Venezuela (116), obtained from cattle, humans, pigs, wild boars, farmed deer, goats, buffaloes, cats, and wild animals. A total of 269 different spoligotypes were found: 142 (8.4%) isolates presented orphan spoligotypes, whereas 1542 (91.6%) formed 113 different clusters. In cattle, SB0140 was the most representative spoligotype with 355 (24.6%) isolates, followed by SB0121 with 149 (10.3%) isolates. Clustering of spoligotypes ranged from 95.2% in Argentina to 85.3% in Mexico. Orphan spoligotypes were also variable, ranging from 23.7% in Mexico to 4.1% in Brazil. A large proportion of spoligotypes were common to the neighboring countries Argentina, Brazil and Chile. In conclusion, despite the diversity of spoligotypes found in the five countries studied, there are major patterns that predominate in these neighboring countries. These clusters may reflect a long-lasting active transmission of bovine tuberculosis or common historical origins of infection.